Left atrial appendage closure with Watchman device in prevention of thromboembolic complications in patients with atrial fibrillation: First experience in Serbia - Nedeljković, Milan A.; Beleslin, Branko; Tešić, Milorad; Vujisić Tešić, Bosiljka; Vukčević, Vladan; Stanković, Goran; Stojković, Siniša; Orlić, Dejan; Potpara, Tatjana; Mujović, Nebojša; Marinković, Milan; Petrović, Olga; et al. (Vojnosanitetski pregled, 2017)
Introduction. Atrial fibrillation (AF) is the major cause of stroke, particularly in older patients over 75 years of age. European Society of Cardiology guidelines recommend chronic anticoagulation therapy in patients with atrial fibrillation if CHA2DS2-VASc score is ≥ 1 [CHA2DS2-VASc score for estimating the risk of stroke in patients with non-rheumatic AF consisting of the first letters of patients condition: C – congestive heart failure; H – hypertension; A2 – age ≥ 75 years; D – diabetes mellitus; S2 – prior stroke, transitory ischaemic attack (TIA) or thrombolism; V – vascular disease; A – age 65–74 years; Sc – sex category]. However, a significant number of patients have a high bleeding risk, or are contraindicated for chronic oral anticoagulation, and present a group of patients in whom alternative treatment options for thromboembolic prevention are required. Transcatheter percutaneous left atrial appendage closure (LAAC) devices have been recommended in patients with contraindications for chronic anticoagulant therapy. Case report. We present our first three patients with nonvalvular AF and contraindications for chronic anticoagulant therapy who were successfully treated with implantation of LAAC Watchman device in Catheterization Laboratory of the Clinic for Cardiology, Clinical Center of Serbia in Belgrade Conclusion. Our initial results with Watchman LAAC device are promising and encouraging, providing real alternative in patients with non-valvular AF and contraindication for chronic anticoagulant therapy and high bleeding risk.